On the Effectiveness of Child Care Centers in Promoting Child Development in Ecuador - Jose Rosero (Tinbergen Institute, 2012)
Although the literature on the effectiveness of child care centers in developing countries is thin, most of the studies have concluded that the provision of these services are beneficial to enhance the development of poor children at early ages. Using different matching techniques, the results in this paper contrast with that conclusion as it finds no support of a positive effect of a large scale child care program in Ecuador on any of the dimensions considered of cognitive development. This paper also provides evidence that the program increased mother's labor force participation and family income but reduced health outcomes of children. The results are in line with the ones found in (Rosero and Oosterbeek, 2011) and support the existence of a trade-off between children development and labor market participation that should be considered at the moment of designing and implementing social policies.
Keywords: J13; I28; H40; O12; 330; Early childhood development; child care centers; propensity score matching; developing country; Ecuador